Parametric Study of the Effect of Diameter-to-Thickness Ratio Against Bending and Shear Load on the Behavior of Round Hollow Structural Section Beam - Kori Effendi, Mahmud; Yulianto, Hariadi (Journal of the Civil Engineering Forum, 2024)
The steel-constructed buildings in Indonesia are on the rise, indicating a growing preference for their durability and versatility in construction projects. This led to the general application of Round Hollow Structural Section (Round HSS) as column and beam elements. Therefore, this study aimed to conduct parametric analysis of the effect of Diameter-to-Thickness Ratio (D t-1) on the three-point and four-point flexural analysis of Round HSS beam using MSC Marc/Mentat software. Nonlinear materials and geometries were employed, along with the application of contact analysis, with contacted and contacting bodies. Moreover, the load and boundary condition were set to be similar to the experiment. The results showed that a greater D t-1 led to the possibility of withholding a smaller load and causing smaller displacement in Group A with fixed diameter and different thickness values. Meanwhile, in Group B with fixed thickness but different diameters, a greater D t-1 led to the potential of restraining more load and experiencing smaller displacement. All specimens from both groups were observed to have failed due to a combination of global and local buckling at the right location under the load applied. AISC bending moment calculated was found to be greater than the values obtained from the finite element analysis for all sections under three-point loads. It was also discovered in the four-point flexural analysis that the bending moment of noncompact section was greater than for AISC while those for the compact section were lower. Furthermore, shear strength (Vn) calculated was observed to be greater thanshear force from finite element analysis (Pmax/2).